Computational and Robustness Reproducibility of "UN Peacekeeping and Democratization in Conflict-Affected Countries" - Christian Oswald; Julian Walterskirchen (Institute for Replication (I4R), 2024)
Blair et al. (2023) examine the effect of UN peacekeeping on democratization in conflict-affected countries. They use fixed effects and instrumental variable estimators and find evidence that "UN missions with democracy promotion mandates are strongly positively correlated with the quality of democracy in host countries but that the magnitude of the relationship is larger for civilian than for uniformed personnel, stronger when peacekeepers engage rather than bypass host governments when implementing reforms, driven in particular by UN election administration and oversight, and more robust during periods of peace than during periods of civil war". Since the authors provide an impressive list of robustness checks, we focus on computational and robustness reproducibility. We replicate the findings using the Stata code provided in the replication material and reproduce all main analyses in R. We add year fixed effects to country fixed effects, cluster standard errors, use fixed and random panel regression estimators and ordered Beta regression estimators. We furthermore reproduce instrumental variable estimators with two different packages. We find that the original findings were reproducible and robust.
Keywords: 330; peacekeeping; democratization; civil war